Third order symmetrical microstrip dual-behaviour resonator filter at 6GHz / Ahmad Farhan Ahmad - Ahmad, Ahmad Farhan (2010)
This paper is aimed on the design of microstrip dual-behaviour resonator (DBR) filter. The design is a third order filter developed at the center frequency 6 GHz. The bandwidth of the dual-behaviour resonator filter is 7%. Dual-behavior resonators (DBRs) are based on the parallel association of two different bandstop structures, which implies a constructive recombination. This filter is design by using relative permittivity, cr =5.4 and substrate thickness, h= l .6mm. Simulations are proposed throughout the paper to illustrate the various possibilities offered by the concept. Experimental results in microstrip technology are also presented in order to validate the idea.